The Analysis of User Acceptance Using UTAUT and Delone & McLean Model: Study Case of Banking Mobile Application - Agus Rofi'i; Dede Ridho Firdaus; Irwan Moridu (Journal of Information System, Technology and Engineering, 2023)
This study aims to determine the acceptance of the use of mobile banking applications and analyze the factors that influence their acceptance. The models proposed in this study are the UTAUT and Delone & McLean integration models. The criteria for respondents in this study were mobile banking users for at least 4 months and using purposive sampling. Data analysis was carried out using the PLS-SEM approach. In this study, 5 of the 8 hypotheses were accepted. Then, the factors that affect the acceptance of mobile banking users are obtained, namely performance expectancy, social influence, service quality, and information quality. Then the factors that do not affect user acceptance are effort expectancy, facilitating conditions, and system quality. The findings of this study are that 78.3% of users accept that they want to use mobile banking in the future and recommend it to mobile banking developers in the hope that in the future the application will be easier to understand, compatible with all smartphone systems that are used by many people, and system quality will be improved to minimize constraints on the application.